Can we find a good biochemical marker of early cardiotoxicity in children treated with haematopoietic stem cell transplantation? - Zaucha-Prażmo, Agnieszka; Sadurska, Elżbieta; Drabko, Katarzyna; Kowalczyk, Jerzy R. (Contemporary Oncology/Współczesna Onkologia, 2016)
Cardiotoxicity is one of the complications following haematopoietic stem cell transplantation (HSCT), but its diagnosis may be hampered due to the presence of different post-transplant comorbidities. The aim of the study was to assess the incidence of cardiac complications and the significance of biochemical markers (NT-proBNP, ANP, ET-1, and TnI) and ECHO systolic and diastolic parameters analysis in children treated with HSCT. Thirty consecutive children (median age 9.6 years) were included in the study. The control group consisted of 14 healthy children (median age of 10.9 years). None of the transplanted children developed clinical cardiotoxicity. Median ET-1 and NT-proBNP plasma levels were elevated when compared to controls in at least 3 out of 4 analysed time points, median ANP levels differed only in one time point, and no difference was found between median TnI values in all analysed time points. Echocardiographic systolic parameters were within the normal range, while median E/A ratio assessed before HSCT, on day +30, and +100 post-transplant was statistically lower in HSCT patients (respectively, 1.34, 1.37, and 1.42 vs. 1.73). It confirms the need for careful follow up in patients who have received chemotherapy and have been treated with HSCT.